إصلاح نظام البحث العلمي الجزائري في عهد الرئيس عبدالعزيز بوتفليقة "1999-2019" - الحمداني، كفاح عباس رمضان (جامعة الموصل - مركز الدراسات الإقليمية, 2024)
يهدف هذا البحث إلى تسليط الضوء على واقع نظام البحث العلمي في الجزائر واهم القرارات الحكومية لإصلاح هذا النظام، وأبرز العقبات التي تواجهه عملية الإصلاح وأبرز الحلول المقترحة لمعالجة العقبات التي تواجه عملية إصلاح نظام البحث العلمي الجزائري. وتنطلق أهمية البحث من أن تطوير التعليم والبحث العلمي تعد من اهم القضايا التي تشغل تفكير الباحثين والحكومات على حد سواء، إذ أصبح كل منهم يدرك تمام الدور الذي يلعبه هذا القطاع في تطوير المجتمعات وتقدمه بما يضمن له الرفاهية الاقتصادية والاجتماعية. وما تزال الجزائر كباقي الدول العربية في بداية الطريق في هذا المجال. فمنذ استقلالها عملت الحكومة فيها على رسم مسار تنموي يهدف إلى تطوير القطاعات الحكومية ومن ضمنها قطاع التعليم العالي والبحث العلمي والتكنولوجي. فضلا عن مجموعة من القوانين الإصلاحية أخرى أهمها زيادة الإنفاق الحكومي لهذا القطاع مع العمل على تطوير عدد المراكز البحثية وزيادة الإنتاج العلمي. لكن مع كل الجهود التي بذلتها الحكومات المتعاقبة في تطوير هذا المجال إلا أن هذا القطاع يواجه العديد من المشاكل التي تحد من تطوره. This research aims to shed light on the reality of the scientific research system in Algeria and the most distinguished government decisions to reform this system, the most difficult obstacles facing the reform process, and the most prominent proposed solutions to address the obstacles facing the reform of the Algerian scientific research system. The importance of research stems from the fact that the development of education and scientific research is one of the key issues that excite the interest of researchers and governments alike, as each of them has become fully aware of the role played by this sector in the development and progress of societies to ensure economic and social well being. Algeria, like other Arab countries, is still at the beginning of the road in this area. Since its independence, the government has worked for a development path aimed at developing government sectors, including higher education and scientific and technological research as well as a set of other reform laws, the most important of which is to increase government spending for this sector while developing many research centers and increasing scientific production. But despite all the efforts made by successive governments in developing this sector, it still faces many problems that limit its development.
Keywords: إصلاح التعليم -- التعليم الجامعي -- البحث العلمي -- الإصلاحات الحكومية